The behaviorally informed organization - Soman, Dilip; Yeung, Catherine, 1976- (Toronto ; Buffalo ; London : University of Toronto Press, 2021)
'Every organization is fundamentally in the business of behavior change. Whether it be a government trying to get business to comply with environmental regulation, a business trying to get its customers to be loyal to their products, or a financial advisor encouraging a client to start saving for retirement, behavior change is critical to organizational success. Despite its centrality to organizations, we do not have a good scientific framework for behavior change or a good understanding of how organizations can embed insights from behavioral science into their operations. To overcome this void, this book develops an overarching framework for using behavioral science. It shows how behavioral insights (BI) can be embedded in organizations to achieve better outcomes, improve the efficiency of processes, and maximize stakeholder engagement. This edited volume will provide an enterprise-wide strategic perspective of how governments, businesses, and other organizations have embedded BI into their operations. It is based on research by academics and practitioners from the Behaviourally Informed Organizations Partnership and will highlight ideas, pragmatic frameworks, and prescriptive outcomes, based on illustrative case studies. Featuring a foreword by Cass Sunstein, this book investigates key findings from BI, with an eye toward how it can be used to solve problems and seize opportunities in diverse organizations.'--
The Science of Using Behavioral Science / Dilip Soman -- Embedding Behavioral Insights in Organizations / Bing Feng, Melanie Kim, and Dilip Soman -- Why Should Organizations Want to Be Behaviorally Informed? / Melaina Vinski -- Gut Check: Why Organizations That Need to Be Behaviorally Informed Resist It / Shannon O'Malley and Kelly Peters -- Seeing Sludge / Daniel Cowen, Niketana Kannan, and Dilip Soman -- A Guide to Guidelines / Sophie Duncan, Melanie Kim, and Dilip Soman -- Boundedly Rational Complex Consumer Continuum / Derek Ireland -- A Scarcity of Attention / Matthew Hilchey and J. Eric T. Taylor -- Workplace Habits and How to Change Them / Kyle Murray and Shirley Chen -- Humanizing Financial Services with Behavioral Science / Jane Howe, Alex Henderson, Jennifer Nachshen, and Sarah Reid -- Choice Architecture in Programs and Policy / Elizabeth Hardy, Lauryn Conway, and Haris Khan -- Helping Low-Income Canadians to File Taxes and Access Benefits / Jennifer Robson -- Online Privacy / Melanie Kim, Kim Ly, and Dilip Soman -- Behavioral Science for International Development / Abigail Dalton, Varun Gauri, and Renos Vakis -- Building Partnerships for Behavioral-Science Initiatives in the Public Sector / Mathieu Audet, Emilie Eve Gravel, Rebecca Friesdorf, and Hasti Rahbar -- Behavioral Science in Policy and Government: A Roadmap / Catherine Yeung and Sharon Tham.
Includes bibliographical references.
Issued also in electronic format.
Keywords: Organizational behavior -- Case studies; Organizational change -- Case studies; Human behavior -- Case studies; Psychology, Industrial -- Case studies; Human behavior; Organizational behavior; Organizational change; Psychology, Industrial; Case studies